hello, I am trying to understand boolean expressions.

Can someone please tell me what the following equates to, so I can see how it works.

not(A) + A.B = ?

I know that not(A) + A = 1, but how do I finish off this one ?

thanks kindly.

Printable View

- May 14th 2011, 02:55 AMfran1942boolean expression
hello, I am trying to understand boolean expressions.

Can someone please tell me what the following equates to, so I can see how it works.

not(A) + A.B = ?

I know that not(A) + A = 1, but how do I finish off this one ?

thanks kindly. - May 14th 2011, 03:36 AMemakarov
I assume that A.B is the conjunction ("and") of A and B. I'll skip the period below and will write ~A for not(A).

~A + AB can be simplified to ~A + B as follows:

~A + AB = ~A(1 + B) + AB = ~A + ~AB + AB = ~A + (~A + A)B = ~A + 1B = ~A + B.

To come up with this, I drew a Venn diagram of ~A + AB to see that it is ~A + B, then double-checked it using truth tables (without writing everything), and finally decided to represent B in the right-hand side, ~A + B, as (~A + A)B because the left-hand side, ~A + AB, contains AB. - May 14th 2011, 12:11 PMfran1942
thanks kindly, I understand now.